Content Appeal’s Influence on TikTok Affiliators’ Engagement - Lutfiyyah, Risya Silky; Christin, Maylanny (Riviera Publishing, 2025)
This study examined the influence of four content appeal dimensions—informative, emotional, visual, and originality—on audience engagement in the context of TikTok affiliate marketing in Indonesia. The research was motivated by the growing trend of public participation in affiliate programs. A quantitative method was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM), based on data collected from 150 respondents. The results showed that informative, emotional, and originality appeals had a positive and significant effect on audience engagement, while visual appeal did not show a significant impact. Originality emerged as the strongest factor in driving interaction. These findings indicate that informative content with emotional depth and original delivery is more effective in fostering engagement than visual content alone. This suggests that visual elements have become a common standard on TikTok, making originality, message clarity, and emotional resonance the key differentiators in capturing audience attention.